THE CORRELATION BETWEEN MOTIVATION AND SPEAKING ABILITY OF THE EIGHTH-GRADE STUDENTS OF SMPN 2 NUSA PENIDA IN ACADEMIC YEAR 2021/2022 - I Gede Dayuh Tanggan; Ida Bagus Nyoman Mantra; AA. Istri. Yudhi Pramawati (Academic Journal on English Studies (AJOES), 2023)
This study aimed at finding out how students’ motivation influenced speaking ability of the eighth-grade students in SMPN 2 Nusa Penida. It made use of a correlation research design. The sample consist of 25 students. They were chosen by random sampling technique. The data which were needed for this research were collected through administering questionnaire about motivation and speaking test as the research instruments and delivered by using What Sapp Group platform. The obtained data were analyzed by investigating the correlation between motivation score and speaking test score which was done by using IBM SPSS Statistic 26. The result of the correlation between motivation and speaking ability was 0.506. It described that there is a significant correlation between motivation and speaking ability of the eighth-grade students of SMPN 2 Nusa Penida in academic year 2021/2022. In conclusion, the alternative hypothesis (Ha) is accepted.